PENERAPAN METODE PEMECAHAN MASALAH UNTUK MENINGKATKAN KREATIVITAS DAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPA TENTANG GAYA GRAVITASI BUMI DI KELAS V SDN 9 LABUAN - Ofan Ofan (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Facts that have occurred in the learning process so far that are responsible in class V SDN 9 Labuan stillhave not provided an opportunity for students to develop creativity and critical thinking abilities of students,especially in learning Natural Sciences (IPA) about the subject of